Enhancing language learning through gamification in linguistically diverse classrooms - Nik Fauzi, Sheela Faizura; Ngien, Ming Ming; Jenny, YapTze Kie; Ismail, Nur Shuhadak (Penerbit UiTM (UiTM Press), 2025)
The effectiveness of Trithasa as a multilingual educational card game in supporting vocabulary acquisition and learner engagement among ESL learners is the focal point of this study. In response to the increasing need for multilingual competence in globalised settings, it explores how gamification can foster motivation, cross-cultural awareness, and language confidence. Rooted in Vygotsky’s Zone of Proximal Development, a surveybased approach was conducted with 38 undergraduates who used Trithasa over a one-month period. The game, which features English, Arabic, and Mandarin vocabulary supported by audio via QR codes, encourages interactive and selfdirected learning. Findings revealed high levels of learner satisfaction and engagement, particularly in English and Arabic language development, while the impact on Mandarin was comparatively lower. Participants also reported improved cognitive and problem-solving abilities, as well as increased cultural awareness and confidence in multilingualism. However, some respondents found the cognitive demands of the game overwhelming, thus highlighting the need for a more balanced design. Overall, gamification for multilingual language learning has its potential for refinement to optimise cognitive load and inclusivity. Future studies could contribute to the growing body of research on gamification in language education by applying the Application in other linguistically diverse classrooms.